The conditions for democracy in a future South Africa - Stadler, Alfred William (My University, 1989)
It is not inconceivable that the formal institutions of democracy, with universal adult suffrage in a unitary state at the centre, will be introduced in South Africa in the foreseeable future. It is also not beyond the bounds of probability that these formal institutions will be overtaken by a coup d'etat, or a one-party dictatorship which will subordinate or suppress opposition and dissent. This paper is concerned to investigate the most propitious conditions for a stable future democracy in South Africa. Like other similar undertakings, the paper is primarily based on comparative studies rather than on South African political, economic or social material. The main conditions which will be investigated are social, or socio-economic; political; and institutional. The political conditions will be discussed in two intimately related contexts: the one focused on policy, and the other on political power. But it will also become clear that it disputes the assumption made in the earlier literature that it is possible neatly to separate political conditions from social ones, or to assume that the chains of causality can be arranged in a linear fashion. The paper hopefully contributes to political debates going on in this country. It therefore has a political purpose. It also makes the assumption that academic debate may contribute meaningfully to desirable political ends. However, the paper does not, except in a superficial and piecemeal way, consider the extent to which South African conditions provide evidence of emergent properties conducive to democratic stability, or otherwise.
African Studies Seminar series. Paper presented 16 October 1989. Not to be quoted without the Author's permission.
Keywords: South Africa. Politics and government, 1989-1994